Pengaruh Disiplin Kerja dan Motivasi Kerja Terhadap Kinerja Pegawai Bank Mandiri Cabang Menteng Jakarta Pusat - Aslamia, Saibatul; Siska, Elmira (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2025)
Work discipline and work motivation are very important to improve employee performance. The problem faced at Bank Mandiri at Menteng Branch is the lack of employee discipline after using office facilities, such as forgetting to turn off computers and printers after use which results in computers often being slow, thus hampering employee performance. Employees are less motivated in achieving targets so that employee target achievement decreases. The aim of this research is to find out how work discipline and work motivation have an impact on the employees performance of Bank Mandiri at Menteng Branch, Central Jakarta. The research population consisted of 30 people, uses a quantitative approach and collects data through questionnaires. Data analysis uses data quality tests, such as validity and reliability tests, as well as classic assumption tests, such as normality tests, multicollinearity tests, heteroscedasticity tests, linearity tests, and hypothesis tests. The results of the partial t test show that work discipline has a positive impact on the performance of Bank Mandiri employees at the Menteng Branch, (calculated t as of 2.599 is greater than the t table as of 2.051) with a significant value of 0.015 which smaller than 0.05). Work motivation also has has a positive impact on the performance of Bank Mandiri employees at the Menteng Branch (calculated t as of 2.520 is greater than the t table as of 2.051) with a significant value of 0.018 which smaller than 0.05).